Preliminary study on Copper, Zinc and Iron concentration in soils from waste dumping site in Tanah Merah, Kelantan, Malaysia (Journal of Tropical Resources and Sustainable Science (JTRSS), 2020)
Soil is a complex matrix and a major reservoir of contamination. It can bind many potential toxic elements such as heavy metals, and they can exist in various forms. The main objective was to characterize the soil sample in relation to heavy metal concentrations in the Tanah Merah waste dumping site. Soil samples were taken from three different locations around the waste dumping site and determined by Atomic Absorption Spectrophotometry (AAS) for Cu, Fe and Zn determination. High concentrations of Fe (9.18 mg/L) as compared to Cu (0.53 mg/L), and Zn (0.49 mg/L) were found in the soil samples but were lower than previous studies. However, early precautionary actions need to be implemented since a higher volume of waste disposal in the future might cause changes in heavy metals intensity at the waste dumping site.
Keywords: Heavy metals; soil; waste dumping site; Tanah Merah; Kelantan; Malaysia